Jikradia olitoria ([Hemiptera]:[Cicadellidae]) Transmits the Sequevar NAGYIIIβ Phytoplasma Strain Associated with North American Grapevine Yellows in Artificial Feeding Assays. Issue 1 (2nd January 2019) - Lenzi, Paolo; Stoepler, Teresa M; McHenry, Diana J; Davis, Robert E; Wolf, Tony K
Abstract: North American Grapevine Yellows (NAGY) is a destructive disease of grapevines caused by phytoplasmas, wall-less bacteria that are insect-transmitted and found in plant phloem tissues. Although the disease was recognized in vineyards in the eastern United States since the 1980s, the identities of vectors remain unknown. The objectives of this study were to survey potential phytoplasma vector insects inhabiting Virginia vineyards that expressed NAGY symptoms and to evaluate their ability to transmit phytoplasmas associated with NAGY. Phytoplasmas were identified as ' Candidatus Phytoplasma pruni'-related NAGYIIIβ strains and ' Ca . Phytoplasma asteris'-related NAGYI-B strains. To determine the identities of the potential vectors, artificial feeding solution was used to evaluate the ability of leafhopper species to release phytoplasmas during feeding and phytoplasma strains were identified using molecular tools. Out of 49 insect species screened, Jikradia olitoria was the only insect that released phytoplasmas into the feeding solutions; all phytoplasmas, thus, detected were identified as NAGYIIIβ strains by nucleotide sequencing of three different genomic regions. No NAGYI-B strain was detected. To our knowledge, this is the first evidence of a potential insect vector of a specific phytoplasma associated with NAGY disease, and it is the first report of J. olitoria being a putative vector of a plant pathogenic phytoplasma.